Gender Differences in Metabolic Syndrome Risk Factors Based on International Diabetes Federation Criteria - Khamail A. Bader; Majid A. Maatook; Ibrahim A. Zaboon (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Metabolic syndrome (MetS) represents a cluster of interrelated metabolic and cardiovascular risk factors that substantially increase morbidity and mortality worldwide. Specific Background: In Iraq, the rising burden of non-communicable diseases has intensified interest in MetS, yet evidence on gender-specific risk patterns using International Diabetes Federation (IDF) criteria remains limited. Knowledge Gap: Few studies have systematically examined gender differences in MetS risk factors among Iraqi adults. Aims: This study aimed to identify and compare gender-specific risk factors for MetS among adults in Al-Basra province based on IDF criteria. Results: Distinct gender differences were observed in sociodemographic characteristics, anthropometric measures, lipid profiles, blood pressure, smoking status, and family history patterns, while age, residence, body mass index, glycemic status, and physical activity showed no significant gender differences. Novelty: The study provides localized, gender-stratified evidence on MetS risk factors in southern Iraq. Implications: The findings support the need for gender-sensitive prevention, screening, and management strategies within primary care and public health programs.Keywords : Metabolic Syndrome, Gender Differences, Risk Factors, International Diabetes Federation Criteria, Waist CircumferenceHighlight : Females showed higher LDL, HDL, and familial hypertension, diabetes, and cardiovascular histories. Males exhibited greater waist measurements, smoking prevalence, and familial obesity history. Anthropometric measures differed by sex, while body mass index and physical activity remained comparable.